Urgency of Expanding the Meaning of State Financial Losses Based on Ecological Losses Resulting from Corruption in the Natural Resources Sector - Jiwanti, Ainun; Mona Ervita (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the urgency of expanding the meaning of state financial losses by including ecological losses resulting from corruption in the natural resource sector based on an ecocentric approach. This study uses a normative juridical method with a statute approach, a case approach, and a conceptual approach. The novelty of this study lies in the use of an ecocentric approach in the concept of state financial loss, which asserts that natural resources are part of state wealth, so their damage due to corruption in the natural resource sector must be considered as state financial loss. However, this contradicts the current legal approach, which only recognizes “actual loss” based on Constitutional Court Decision No. 25/PUU/XIV/2016, thereby hindering the recognition of ecological losses as part of state financial losses. The results of the study show that corruption in the SDA sector not only has an impact on state financial losses but also causes severe environmental damage. However, current law enforcement still uses an anthropocentric approach that only considers state losses in financial terms without including ecological damage caused by SDA corruption as part of state financial losses, so there is an urgent need to expand the meaning of state financial losses to include ecological losses. The conclusion of the research suggests that incorporating ecological losses into the calculation of state financial losses ensures that criminal law enforcement holds corrupt actors accountable not only for financial aspects but also for environmental restoration, thereby supporting ecological justice and the sustainability of natural resources.